Figure drawing atelier : an instructional sketchbook - Aristides, Juliette (Monacelli Studio, 2019)
"Figure Drawing Atelier offers a comprehensive, contemporary twist to the very traditional Atelier approach to the methods that instruct artists on the techniques they need to successfully draw and ultimately paint the figure. The book offers art instruction, practical and progressive lessons on drawing the figure, and high-quality, sketchbook paper in a beautiful package that includes blank pages for sketching and copying. Artists will then have a record of their process, like with a sketchbook, which many artists like to document and save. In this elegant and inspiring workbook, master contemporary artist and author Juliette Aristides breaks down the figure drawing process into small, manageable lessons; presents them progressively; introduces time-tested principles and techniques in the Atelier tradition that are easily accessible; and shares the language and context necessary to understand the artistic process and create superior, well-crafted drawings"--